Brand Image Terhadap Minat Konsumen Mobil Isuzu Panther - Dodi Agusra (COSTING : Journal of Economic, Business and Accounting, 2019)
Business people in the automotive industry continue to strive for what they produce and offer, desired and received by consumers, which will then be purchased at the maximum purchase level with a high frequency of purchases. The research objective was to determine the effect of brand image on consumer interest in buying Isuzu Panther cars at PT. Astra International Tbk. Pekanbaru Branch. The research method used in this study is multiple linear regression analysis. The results of the study concluded that respondents agreed with the brand image of the Isuzu Panther car today as a fuel-efficient car, a quality car, suitable for all terrain so that it adds to the rider's confidence and is an easy car to maintain and repair. Consumer interest in Isuzu Panther cars is considered good or interested consumers. The analysis using SPSS showed that the brand image has a very strong relationship with consumer interest in buying Isuzu Panther cars. Brand image has a positive effect on consumer interest, so if there is an increase in the brand image of the Isuzu Panther car, it will also lead to an increase in consumer interest in buying Isuzu Panther cars Keywords : Brand Image, Consumer Interest, Isuzu Panther